2008
DOI: 10.1073/pnas.0802176105
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Hoxb8 alters spinal dorsal laminae and sensory responses in mice

Abstract: Although Hox gene expression has been linked to motoneuron identity, a role of these genes in development of the spinal sensory system remained undocumented. Hoxb genes are expressed at high levels in the dorsal horn of the spinal cord. Hoxb8 null mutants manifest a striking phenotype of excessive grooming and hairless lesions on the lower back. Applying local anesthesia underneath the hairless skin suppressed excessive grooming, indicating that this behavior depends on peripheral nerve activity. Functional ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 26 publications
1
56
1
Order By: Relevance
“…Serotonergic neuron generation also relies on Hox-dependent programs (Pattyn et al, 2003) while Hox2 paralog genes control oligodendrocyte production (Miguez et al, 2012). At spinal levels, Hoxb8 has been implicated in the organization of dorsal horn neurons that relay nociceptive stimuli at lumbar levels, survival of the second spinal ganglion and the specification of noradrenergic sympathetic neurons of the autonomic nervous system (Holstege et al, 2008; Huber et al, 2012; van den Akker et al, 1999) while Hoxb13 acts to define the caudal boundary of the spinal cord (Economides et al, 2003). …”
Section: Hox Expression and Function In The Nervous Systemmentioning
confidence: 99%
“…Serotonergic neuron generation also relies on Hox-dependent programs (Pattyn et al, 2003) while Hox2 paralog genes control oligodendrocyte production (Miguez et al, 2012). At spinal levels, Hoxb8 has been implicated in the organization of dorsal horn neurons that relay nociceptive stimuli at lumbar levels, survival of the second spinal ganglion and the specification of noradrenergic sympathetic neurons of the autonomic nervous system (Holstege et al, 2008; Huber et al, 2012; van den Akker et al, 1999) while Hoxb13 acts to define the caudal boundary of the spinal cord (Economides et al, 2003). …”
Section: Hox Expression and Function In The Nervous Systemmentioning
confidence: 99%
“…HoxB8 -null animals self-groom excessively and also have increased social grooming of control animals. A subsequent report from another group using a different Hoxb8 null mouse line suggested that deficits in spinal cord function led to changes in sensitivity to pain, potentially underlying the excessive, self-injurious grooming behavior (Holstege et al, 2008). A follow-up study conducted by the Capecchi group in the original Hoxb8 null mice, however, clearly demonstrated that central nervous system function was responsible for excessive grooming in these animals (Chen et al, 2010).…”
Section: Genetic Mouse Models Of Ocdmentioning
confidence: 99%
“…For instance, gene manipulation of Hoxb8, a homeobox-containing transcription factor, resulted in abnormalities in the obsessivecompulsive disorder circuit in the central nervous system, ontogenesis, and development of the upper cervical DRG and the nociceptive response (73)(74)(75). Kifc2 is a neuron-specific C-terminal kinesin superfamily motor for the transport of multivesicular body-like organelles in dendrites (76).…”
Section: Discussionmentioning
confidence: 99%